Occurrence Mechanism of Convective Geothermal Systems in Jiaodong Peninsula, China - Shi, Meng; Kang, Fengxin; Yin, Tao; Gao, Song; Sui, Haibo; Guo, Xu; Yu, Xiaojing (Frontiers in Earth Science, 2022)
Previous studies have shown that on the surface, Jiaobei uplift and Weihai uplift have higher heat flow values than Jiaolai depression. However, the mechanism by which the deep heat flow migrates and the exposure of geothermal resources are still unclear. In this study, the geothermal field distribution, thermal conductivity, temperature logging data, and chemical composition of the geothermal fluid in the Jiaodong Peninsula were analyzed. Regarding the thermal field’s characteristics and their controlling factors, a conceptual model of heat flow diversion- accumulation between the uplift and basin areas in the Jiaodong Peninsula is proposed. The lithology of the uplift area is mainly composed of intrusive rocks and metamorphic rocks with high thermal conductivities. The lithology of the basin mainly consists of sandstone with a low thermal conductivity. The bottom of the basin, which has a low thermal conductivity and low permeability, serves as a heat insulation and water insulation roof, which causes the heat flow and the heat-carrying fluids and gases from the deep crust to be refracted and redistributed at the bottom of the basin area. As a result, the bottom of the uplift areas has a higher heat flow. In particular, the axial position in the uplift area has the highest heat flow. In addition, the geothermal resources in the Jiaodong Peninsula are mainly distributed in the V-shaped area where the upper block of the NE- and NW-trending faults intersect, and the scope of the exposure of the geothermal resources is very limited.